Gimkit As A Gamification Media In Islamic Religious Education: It’s Impact On Student Learning Outcomes - Musfirah Daud Pisba, Syauqi; Rahmanto, Muhammad Arifin (JURNAL PEDAGOGY, 2025)
This study aims to (1) determine the effect of Gimkit media as a gamification assessment tool in PAI learning on student learning outcomes and (2) determine the difference in student learning outcomes between Gimkit media and Google Forms media. The research method used was a quasi-experimental nonequivalent group design. The sample consisted of an experimental class and a control class of 35 students each at As-Syafi'iyah 01 Islamic High School in Jakarta. Data were collected through pre-test and post-test questions and analysed using descriptive test, normality test, homogeneity test, paired sample t-test and independent sample t-test. The results showed that there was an effect of Gimkit media in improving students' learning outcomes significantly with a value of 0.000 <0.05 and the average difference in learning outcomes between Gimkit and Google Forms media with a value of 85.71 and 76.86. Based on these findings, it can be concluded that Gimkit media has an effect on improving student learning outcomes and Gimkit can be used as a medium to improve the quality of PAI learning. This research adds to the literature on the effectiveness of gamification in education and opens up opportunities for further research in other subjects or in different learning contexts.